2019
DOI: 10.1016/j.sjopt.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of PON2 and PON3 polymorphism with risk of developing cataract

Abstract: Purpose Paraoxonases (PON) are calcium bound enzymes offering protection against oxidative stress by working as endogenous free-radical scavenging molecules. Oxidative stress has been implicated in pathophysiology of many diseases including cataract. Lens opacity is an age related disorder which is a principal cause of blindness in Pakistani population. Relationship of PON2 and PON3 polymorphism with genetic predisposition for incidence of cataract has not been investigated till date. Objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…A combined genotype analysis for PON2 polymorphisms revealed that the combination of G148 and S311 was more frequent in cataract subjects, whereas heterogeneous alleles at 311 and 148 were more likely to be present in subjects without lens opacity. It seems likely that the presence of mutations at 148 and 311 positions might be considered as a risk factor for the development of cataracts [48]. The PON2 gene polymorphisms A148G and S311C have been independently associated with diabetic nephropathy in type II diabetic patients.…”
Section: Pon2 Snpsmentioning
confidence: 99%
“…A combined genotype analysis for PON2 polymorphisms revealed that the combination of G148 and S311 was more frequent in cataract subjects, whereas heterogeneous alleles at 311 and 148 were more likely to be present in subjects without lens opacity. It seems likely that the presence of mutations at 148 and 311 positions might be considered as a risk factor for the development of cataracts [48]. The PON2 gene polymorphisms A148G and S311C have been independently associated with diabetic nephropathy in type II diabetic patients.…”
Section: Pon2 Snpsmentioning
confidence: 99%
“…Ala/Gly at position 148 and Ser/Cys at position 311 are two of the polymorphisms of PON2 that are often detected [26] and these polymorphisms are associated with its decreased lactonase activity [34]. It appears likely that the existence of mutations at the 148 and 311 sites could be regarded as a risk factor for the onset of cataracts [35]. The PON2 gene polymorphisms A148G and S311C have been independently linked to diabetic nephropathy in type II diabetic patients [36].…”
Section: Discussionmentioning
confidence: 99%